Cost‐effectiveness of hepatitis C virus (HCV) elimination strategies among people who inject drugs (PWID) in Tijuana, Mexico. (22nd March 2021) - Marquez, Lara K.; Fleiz, Clara; Burgos, Jose Luis; Cepeda, Javier A.; McIntosh, Craig; Garfein, Richard S.; Kiene, Susan M.; Brodine, Stephanie; Strathdee, Steffanie A.; Martin, Natasha K.
Abstract: Background and Aims: In Latin America, Mexico was first to launch a hepatitis C virus (HCV) elimination strategy, where people who inject drugs (PWID) are a main risk group for transmission. In Tijuana, HCV seroprevalence among PWID is > 90%, with minimal harm reduction (HR). We evaluated cost‐effectiveness of strategies to achieve the incidence elimination target among PWID in Tijuana. Methods: Modeling study using a dynamic, cost‐effectiveness model of HCV transmission and progression among active and former PWID in Tijuana, to assess the cost‐effectiveness of incidence elimination strategies from a health‐care provider perspective. The model incorporated PWID transitions between HR stages (no HR, only opioid agonist therapy, only high coverage needle–syringe programs, both). Four strategies that could achieve the incidence target (80% reduction by 2030) were compared with the status quo (no intervention). The strategies incorporated the number of direct‐acting anti‐viral (DAA) treatments required with: (1) no HR scale‐up, (2) HR scale‐up from 2019 to 20% coverage among PWID, (3) HR to 40% coverage and (4) HR to 50% coverage. Costs (2019 US) and health outcomes [disability‐adjusted life years (DALYs)] were discounted 3% per year. Mean incremental cost‐effectiveness ratios (ICER, /DALY averted) were compared with one‐time per capita gross domestic product (GDP) (9698 in 2019) and purchasing power parity‐adjusted per capita GDP (4842–13 557) willingness‐to‐pay (WTP) thresholds. Results: DAAs alone were the least costly elimination strategy [173 million, 95% confidence interval (CI) = 126–238 million], but accrued fewer health benefits compared with strategies with HR. DAAs + 50% HR coverage among PWID averted the most DALYs but cost 265 million, 95% CI = 210–335 million). The optimal strategy was DAAs + 50% HR (ICER 6743/DALY averted compared to DAAs only) under the one‐time per‐capita GDP WTP (9698). Conclusions: A combination of high‐coverage harm reduction and hepatitis C virus treatment is the optimal cost‐effective strategy to achieve the HCV incidence elimination goal in Mexico.